Analysis of the Fatty Acid Profile in Cream, Buttermilk Fractions, and Anhydrous Milk Fat: Influence of Physicochemical and Microbiological Parameters on the Fatty Acid Profile - Gaja Gużewska; Maciej Monedeiro-Milanowski; Aleksandra Bogumiła Florkiewicz; Izabela Arendowska; Justyna Walczak-Skierska; Dorota Białczak; Paweł Piotr Pomastowski (Applied Sciences, 2024)
This study analyzes the impact of physicochemical parameters on the microbiological and fatty acid profiles of cream, buttermilk, and anhydrous milk fat. Using gas chromatography coupled with mass spectrometry (GC-MS), the fatty acids present in these dairy products were qualitatively determined, highlighting the differences associated with the processing stages. Specifically, the distribution of short-chain, medium-chain, and long-chain fatty acids, such as butyric, caproic, caprylic, capric, lauric, myristic, palmitic, stearic, oleic, and linoleic acids, were analyzed, assessing their nutritional implications. The microbiological composition of the samples was also analyzed using MALDI-ToF MS. The presence of lipolytic bacteria, such as Serratia monocytogenes, which can negatively impact the oxidative stability of fats, was detected. The results show that both environmental and processing conditions significantly affect the quantity and quality of fatty acids, thereby influencing the overall dietary value of dairy products. These findings offer insight into developing improved dairy product formulations that may lead to enhancement of their health benefits.